1999
DOI: 10.1165/ajrcmb.20.4.3342
|View full text |Cite
|
Sign up to set email alerts
|

Lung Fibrosis Induced by Silica Particles in NMRI Mice Is Associated with an Upregulation of the p40 Subunit of Interleukin-12 and Th-2 Manifestations

Abstract: Interleukin (IL)-12 is a cytokine produced principally by activated macrophages which is involved in control of the T-helper 1/T-helper 2 cell (Th1/Th2) polarization of immune responses. To examine its potential involvement in the development of lung fibrosis, we examined the expression (protein, messenger RNA [mRNA]) of IL-12 (p70) and of its subunits (p40 and p35) in lung homogenates, bronchoalveolar lavage fluid (BALF), and bronchoalveolar lavage (BAL) cell cultures in mouse models of resolutive alveolitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
54
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 31 publications
8
54
1
Order By: Relevance
“…Consistent with previous studies (34,36), silica instillation also triggered a significant increase in the level of KC in BAL ( p Ͻ 0.01; Fig. 6).…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies (34,36), silica instillation also triggered a significant increase in the level of KC in BAL ( p Ͻ 0.01; Fig. 6).…”
Section: Figuresupporting
confidence: 92%
“…As previously described (26), silicosis was induced by instilling 2.5 mg of silica via an intratracheal catheter into the lungs of normal BALB/c mice. The resultant inflammatory response peaked 3 days later, and was characterized by a pulmonary infiltrate dominated by neutrophils and the production of inflammatory cytokines and chemokines (26,34,35). To assess whether treatment with suppressive ODN reduced this inflammation, two doses of suppressive ODN were administered one day before silica installation (this treatment regimen was selected on the basis of successful preliminary experiments).…”
Section: Suppressive Odn Inhibit Silica-induced Pulmonary Inflammatiomentioning
confidence: 99%
“…Although IL-4 expression was unchanged or decreased, Davis and colleagues (12) showed an increased IFN-␥ response in the lung of mice with silicosis, suggesting a Th1-like lymphocyte-mediated immune response. Opposite results showed that in wild-type animals, silica-induced fibrosis was correlated with markers of a Th2-like response such as upregulation of IL-4 levels in lung tissue and an increased immunoglobulin IgG1/IgG2a ratio in BAL (24). In the present study, BALF IgG2a levels (Th1) were not modified after silica or AdIL-10 administration.…”
Section: Discussioncontrasting
confidence: 42%
“…IL-12p40 has been found to be produced largely by activated pulmonary macrophages during the fibrotic reaction (23). In this study, we report in the C57BL/6 strain that experimental silicosis is also related with increased IL-12p40 levels, but, in contrast, with a parallel decrease of IL-12p70 content (Fig.…”
Section: Discussionmentioning
confidence: 50%